Student Perception of Learning English Online - Pécsi, Kinga Tünde (Central European Journal of Educational Research, 2021)
The aim of this research was to highlight the impact of online education on teaching and learning English as a foreign language among students aged 12-19, and to research the importance of learner autonomy and motivation in the online teaching – learning process. In order to collect data from the 81 subjects, members of five different classes and age groups, a questionnaire created in Google Forms was used. The questionnaire was designed to provide information about the students’ attitude and motivation for studying English in an online context, autonomy and effort invested in the learning process. Student progress was measured using the end of semester grades of the first semester of the 2019/2020 year compared to those of the first 2020/2021 semester. Results reveal the importance of perceived choice as a factor that supports learner autonomy and learner motivation. The limitations of the study are due to the fact that the students’ level of English and their previous knowledge of the subjects studied online had not been tested beforehand as the current pandemic situation was not foreseeable.